2014
DOI: 10.1002/iid3.20
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thymic stromal lymphopoietin and IL‐3 on human eosinophil–basophil lineage commitment: Relevance to atopic sensitization

Abstract: An important immunopathological hallmark of allergic disease is tissue eosinophilic and basophilic inflammation, a phenomenon which originates from hemopoietic progenitors (HP). The fate of HP is determined by local inflammatory cytokines that permit “in situ hemopoiesis,” which leads to the accumulation of eosinophils and basophils (Eo/B). Given that recent evidence supports a critical immunomodulatory role for thymic stromal lymphopoietin (TSLP) in allergic inflammation, as well as TSLP effects on CD34+ prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 55 publications
(95 reference statements)
0
33
0
1
Order By: Relevance
“…TSLP can promote murine and human bone marrow progenitor cells to differentiate into basophils. 7 Human peripheral CD34 1 cells preincubated with IL-3 and TNF-a have enhanced sensitivity to TSLP-mediated basophil lineage commitment, 8 and mast cell-activated bone marrow mesenchymal stromal cells produce TSLP, which can enhance the differentiation of CD34 1 progenitors into eosinophil/basophil colonies. 9 Furthermore, in the presence or absence of IL-3, TSLP can induce murine basophil receptor changes, including increased CD69, CD62 ligand, CD11b, CD123, IL-33 receptor, and IL-18 receptor expression.…”
mentioning
confidence: 99%
“…TSLP can promote murine and human bone marrow progenitor cells to differentiate into basophils. 7 Human peripheral CD34 1 cells preincubated with IL-3 and TNF-a have enhanced sensitivity to TSLP-mediated basophil lineage commitment, 8 and mast cell-activated bone marrow mesenchymal stromal cells produce TSLP, which can enhance the differentiation of CD34 1 progenitors into eosinophil/basophil colonies. 9 Furthermore, in the presence or absence of IL-3, TSLP can induce murine basophil receptor changes, including increased CD69, CD62 ligand, CD11b, CD123, IL-33 receptor, and IL-18 receptor expression.…”
mentioning
confidence: 99%
“…Experimental findings with mouse models also support the crucial roles of eosinophils in TSLP-induced systemic Th2 inflammatory response [98]. Meanwhile it is known that, in the presence of IL-3, TSLP significantly stimulates human hematopoietic progenitors via TSLP-TSLPR interactions to produce eosinophils and basophils colony forming units, promoting the involvement of eosinophils in allergic inflammation [99]. Another interesting recent finding is that TSLP can directly stimulate eosinophils to produce and release eosinophil extracellular traps, one of the efficient machineries for extracellular bacterial killing [100].…”
Section: Epithelial or Tissue Stromal Cells Eosinophils And Allergimentioning
confidence: 74%
“…27 In addition, it has been reported that human CD34 þ progenitor cells express the TSLPR, 34,38 and that TSLP signaling cooperates with other hematopoietic cytokines in the differentiation of human CD34 þ cells. 38 Further, TSLP can directly activate human CD34 þ progenitor cells isolated from peripheral tissues. 34,38 These studies suggest that the TSLP-ISH pathway operates to promote type 2 inflammatory responses in humans.…”
Section: Epithelial Cell-derived Cytokines and Ishmentioning
confidence: 98%
“…For example, HSPCs express the TSLPR and TSLP signaling upregulates IL-3Ra on peripheral blood CD34 þ cells, rendering them more responsive to the effects of IL-3, with concomitant functional Eo/B colony forming unit differentiation. 38 Furthermore, TSLP stimulation of, and signaling in, human CD34 þ HSPCs results in the rapid release of high levels of cytokines and chemokines, further contributing to specific lineage commitment and differentiation. 34,38 Related to this, TSLP induces IL-5 þ / IL-13 þ CD34 þ cells to appear in sputum after airway allergen challenge of atopic asthmatics.…”
Section: Ish and Allergic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation